Reconstruction of Restorative Justice Policy in Enforcing DIY Regional Regulation Number 2 of 2017 Based on the Principles of Proportionality - Oktora Wahyu Wijayanto; Suryawan Raharjho (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Law enforcement of DIY Regional Regulation Number 2 of 2017 remains dominated by a repressive, legalistic approach that overlooks substantive justice. Despite the growing application of restorative justice in Indonesia's criminal law system, its integration into regional administrative law enforcement has not been systematically developed, creating a normative gap. This study aims to formulate a reconstruction of restorative justice policy based on the principle of proportionality in the enforcement of regional regulations. Using a normative juridical method with statutory, conceptual, and analytical approaches, this study analyzes primary and secondary legal materials through qualitative interpretation and prescriptive argumentation. Findings reveal that restorative justice remains implicit and non-institutionalized in regional administrative law, while the principle of proportionality has not been optimally applied. The proposed reconstruction integrates dialogue mechanisms, administrative mediation, and proportionality-based parameters as a non-judicial resolution model. This study contributes a normative framework for more adaptive, humanistic law enforcement and strengthens the legitimacy of regional government policy.